UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DENGAN KOMBINASI MEDIA GAMBAR DAN METODE CARD SORT DI MIN 2 PADANGSIDIMPUAN - Rina Juliana (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
AbstractThe problems in this study are whether the application of image media and cart sort learning methods can improve student learning outcomes in PAI subjects at MIN 2 Padangsidimpuan. The purpose of this study is to improve student learning outcomes, especially in Fiqh material in carrying out fard prayer through a combination of picture media and cart sort method. While the usefulness of this study is to improve the quality of Islamic Education in Elementary School learning. The research method that I use is Classroom Action Research (CAR), which is action research conducted in the classroom to improve student learning outcomes. This research was conducted in two cycles. Each cycle consists of steps in planning, implementing, observing, and reflecting. This research was conducted at MIN 2 Padangsidimpuan. Based on the results of the research in the first cycle, the results of research on student activity at the first meeting were still lacking and increased in the next action. Then from the study results in the pre-study the percentage of completeness was only 53.33%, in the first cycle of the first meeting there had not been an increase in learning outcomes, but obtained a percentage of completeness of 33.33%, while the average score in the first meeting cycle was 59.87. Furthermore, at the second meeting the total percentage of completeness was 66.66%. This means that there has been an increase in learning outcomes from 33.33% from the first meeting. While the average value of the second meeting was 70.87. This means that for the average value of student learning outcomes increased by 11% from 59.87 to 70.87. Whereas in the second cycle the results of student activity research have also been increased from before because many students have been motivated in carrying out the learning process. In addition, the learning outcomes in the first cycle of the second meeting obtained 80% completeness with an increase in the first cycle of 13.34%. While the average value obtained in the second cycle of the first meeting was 73.53. Furthermore, at the second meeting achieved 100% learning outcomes with an increase of 20% from the first meeting. While an increase in the average value of student learning outcomes at the second meeting was 84.94. Keywords: Learning Outcomes, Image Media and Card Sort Method